PENGARUH DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPEMIMPINAN SEBAGAI VARIABEL MODERASI - Hartanto, Sawiji -; Widajanti, Erni - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2011)
ABSTRACT This research aims to determine the significant effect between: (1) discipline to employee performance, (2) job environment to employee performance (3) moderate the influence of leadership and discipline job environment employees Karanganyar District Personnel Agency. Regional Personnel Agency employee population District Karanganyar year 2010 amounting to some 54 people. Samples taken all but the head of the District Personnel Agency Karanganyar so that the total sample of 53 persons. Sampling technique with a population research, in which all the members of the sampled population, while the technique of data collecting technique used questionnaire. The results of this research concluded: the first significant effect on the discipline of employee performance. Second the job environment does not significantly influence the performance of employees. Third significantly moderated the effect of leadership on employee performance discipline. But significant leadership did not moderate the influence of work environment on employee performance. Keywords: discipline, job environment, leadership, employee performance.